A companion to organizational anthropology - Caulkins, Douglas; Jordan, Ann. (Hoboken, N.J. : Wiley, 2012)
The first comprehensive guide to anthropological studies of complex organizationsOffers the first comprehensive reference to the anthropological study of complex organizationsDetails how organizational theory and research in business has adopted anthropology's key concept of culture, inspiring new insights into organizational dynamics and developmentHighlights pioneering theoretical perspectives ranging from symbolic and semiotic approaches to neuroscientific frameworks for studying contemporary organizationsAddresses the comparative and cross-cultural dimens.
Imagination-ImagingNeurological Theory of Cultural Learning; Image Process and Meaning-Creation Inside the Brain; What Is Cultural Learning?; Implications for Organizational Studies; Network Theory; Ethnographic Case Study of a Retirement Party at MTC Company; Cognitive and Emotional Connectivity; Conclusion; Note; References; PART II: Methods and Analysis; CHAPTER 6: Social Networks and Organizations; Network Theory; Domains of Network Theorizing; Units of Analysis; Methodology; Data Collection; Visualization; Quantitative Analysis; Conclusion; Notes; References.
Includes bibliographical references and index.
Keywords: Business anthropology; Corporate culture; Business anthropology; Corporate culture; Electronic books